Incidence and predictive factors of hyperventilation syndrome in patients after COVID 19 pneumonia: a prospective cohort study [version 1; peer review: 2 approved] - Salma Mokaddem; Hela CHERIF; Mohamed Ridha Charfi; Ferdaous Yangui; Slim Kalboussi; Soumaya Debiche (F1000Research)
Background This study investigates the incidence and predictive factors of Hyperventilation Syndrome (HVS) in patients after COVID 19 pneumonia, addressing the clinical overlap between these conditions. Methods A one-month prospective study was conducted, tracking survivors of COVID-19 pneumonia. Patients were evaluated for ongoing clinical status, including HVS and post-traumatic syndrome disorder (PTSD), using clinical questionnaires, mMRC, Post-COVID-19 Functional Status (PCFS) Score, Nijmegen score, and PTSD Checklist for DSM-5 questionnaire. Results Our study included 222 patients (median age: 57 years, male predominance 62.6%). Somatic comorbidities, primarily metabolic disorders, were reported in 71.2% of cases. The majority had severe or critical infection forms (78.4%), and 91.9% experienced acute symptoms, with 86.5% having three or more symptom clusters. At one month follow-up, dyspnea (52.9%) and asthenia (21.7%) persisted. Functional limitations (PCFS Grade > 2) were observed in 19.6% of patients. The overall incidence of HVS was 158 per 1000 patients, and PTSD was 445 per 1000 patients. Multivariate logistic regression identified cognitive impairment (acute phase), persistent weight loss (post-COVID-19 phase), PCFS grade > 2, and PTSD as independent factors for developing HVS, with relative risks (RRs) of 3.47 (95%CI [1.48-8.31]; p = 0.004), 11.87 (95%CI [1.25-112.88]; p = 0.031), 3.24 (95%CI [1.34-7.86]; p = 0.009), and 5.98 (95%CI [2.27-15.77]; p < 0.001), respectively. Conclusion HVS is prevalent in the post-COVID-19 phase, affecting 15.6 % of survivors. Identified predictive factors suggest the convergence of psychosomatic pathophysiological mechanisms. Further research is crucial for a detailed understanding of these mechanisms in long COVID-19 patients.